Gender and Climate Change in Uganda: Effects of Policy and Institutional Frameworks - Acosta, M.; Ampaire, Edidah L.; Okolo, Wendy; Twyman, Jennifer (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
In order to obtain an enriched understanding of the framing of gender issues in climate change related policies in Uganda and to explore its impacts on climate change adaptation at grassroots, the International Institute of Tropical Agriculture (IITA) and the International Center for Tropical Agriculture (CIAT) analyzed the influence of current policy and institutional frameworks on gender and climate issues. The study evaluated the institutional and political context under which policies related to climate change are developed and implemented in Uganda as well as examined the gender approaches employed at different administrative levels of the government.